Evaluating the predictive utility of patient‐oriented scoring of atopic dermatitis (PO‐SCORAD) versus Patient‐Oriented Eczema Measure (POEM) for peanut sensitivity in patients with atopic dermatitis - Sara Bilimoria; Kachiu Lee; Peter Lio (Wiley, 2022)
Abstract Background Current Guidelines from the National Institute of Allergy and Infectious Disease (NIAID) are based on the Learning Early About Peanut Allergy Study (LEAP Study) results and recommend early introduction of peanuts to children with atopic dermatitis (AD) depending on their disease severity. There is yet to be a widely accepted method of evaluating AD severity among clinicians. Thus, the purpose of this study was to determine the association between AD severity as measured by patient‐oriented scoring of atopic dermatitis(PO‐SCORAD) and Patient Oriented Eczema Measure (POEM) surveys and peanut sensitivity as measured by Immunoglobulin E (IgE) or skin prick test levels. Objectives The primary objective of this study was to determine the association between AD severity as measured by PO‐SCORAD and POEM surveys and peanut sensitivity as measured by IgE or skin prick test levels. The secondary objective of this study was to determine the rate of peanut sensitisation amongst patients with 'mild AD' as defined by PO‐SCORAD score of 1−27 and a POEM score of 0‐7. Methods Patients between 3 months and 18 years old undergoing IgE or skin prick testing for peanut allergy were recruited from two allergy clinics in the Chicagoland area. Patients or their guardians completed a PO‐SCORAD survey and POEM survey. Results There was no significant difference in AD severity (as measured by PO‐SCORAD or POEM score) between sexes or age groups (<12 months vs. ≥12 months). Moreover, there was no significant relationship found between PO‐SCORAD or POEM scores and rate of peanut sensitivity. Conclusion Despite no significant relationship found between PO‐SCORAD or POEM score and peanut sensitivity, the hypothesis that AD severity can predict risk of peanut sensitivity may still be valid based on a growing body of evidence. The negative results of this study are likely due to the small study population used due to limitations of the COVID‐19 pandemic. Moreover, evaluating AD severity through PO‐SCORAD and POEM surveys may not be ideal for paediatric patients.